Shape-Changing DNA-Linked Nanoparticle Films Dictated by Lateral and Vertical Patterns - Kim, Jongwook; Lee, Sunghee; Choi, Jisu; Baek, Kyungnae; Shim, Tae Soup; Hyun, Jerome Kartham; Park, So Jung (Advanced Materials, 2022)
The self-assembly of nanoscale building blocks into complex nanostructures with controlled structural anisotropy can open up new opportunities for realizing active nanomaterials exhibiting spatiotemporal structural transformations. Here, a combination of bottom-up DNA-directed self-assembly and top-down photothermal patterning is adopted to fabricate free-standing nanoparticle films with vertical and lateral heterogeneity. This approach involves the construction of multicomponent plasmonic nanoparticle films by DNA-directed layer-by-layer (LbL) self-assembly, followed by on-demand lateral patterning by the direct photothermal writing method. The distinct plasmonic properties of nanospheres and nanorods constituting the multidomain films enable photopatterning in a selective domain with precisely controlled vertical depths. The photopatterned films exhibit complex morphing actions instructed by the lateral and vertical patterns inscribed in the film as well as the information carried in DNA.
Keywords: Directed self-assembly; DNA-directed self-assembly; Nanoparticle films; Nanoscale building blocks; Patterning; Photo-thermal; Plasmonic material; Plasmonics; Stimuli-responsive materials; Stimulus-responsive materials; DNA; Nanoparticles; Nanostructures; Nanotubes; DNA-directed self-assembly; gold nanoparticles; patterning; plasmonic materials; stimuli–responsive materials